An infodemiological investigation of the so-called "Fluad effect" during the 2014/2015 influenza vaccination campaign in Italy: Ethical and historical implications. Issue 3 (4th March 2018) - Mahroum, Naim; Watad, Abdulla; Rosselli, Roberto; Brigo, Francesco; Chiesa, Valentina; Siri, Anna; Ben-Ami Shor, Dana; Martini, Mariano; Bragazzi, Nicola Luigi; Adawi, Mohammad
ABSTRACT: Influenza vaccines represent a major tool to contain the clinical and epidemiological burden generated by influenza. However, in spite of their effectiveness, vaccines are victims of prejudices and false myths, which contribute to the increasing phenomenon of vaccine hesitancy and loss of confidence. Media and, mainly, new media, and information and communication technologies play a major role in disseminating health-related information. While, on the one hand, they can be extremely promising in promoting disease prevention, on the other hand, they can also have a negative impact on population's health attitudes and behaviors when delivering information not based on scientific evidences. The "Fluad-case" is an excellent example of the crucial role of an adequate information campaign. Following the cluster of deaths allegedly related to the administration of the adjuvanted influenza vaccine "Fluad" during the 2014–2015 influenza campaign, the Italian health authorities and regulatory bodies decided the withdrawal of two potentially contaminated Fluad batches. This fostered a huge media coverage, with resulted in negatively impacting on influenza vaccination coverage. Monitoring and tracking the Fluad-related web searches, we showed that Liguria resulted the Italian region with the highest number of Fluad-related website searches and that, interestingly, Fluad was searched also in Regions in which this vaccine was not distributed. A positive moderate correlation between accessing Fluad-related websites and overall influenza vaccination coverage was found (r = 0.66 ([95%CI 0.29–0.86], p = 0.0026). Considering subjects ≥65 years, who are the subjects for which the Fluad vaccination is recommended, the correlation resulted r = 0.49 ([95%CI 0.03–0.78], p = 0.0397). As such, health authorities and decision-makers should promote high-quality communication campaigns in order to raise awareness of vaccination practices.